2008
DOI: 10.1007/s10646-008-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic risk assessment of pesticides in surface waters in and adjacent to the Everglades and Biscayne National Parks: I. Hazard assessment and problem formulation

Abstract: An aquatic risk assessment under the U.S. Environment Protection Agency (EPA) ecological risk framework was conducted for atrazine, metolachlor, malathion, chlorpyrifos, and endosulfan in the C-111 freshwater basin (eastern boundary of the Everglades National Park), northeast Florida Bay, and south Biscayne Bay in South Florida. Based on the use of the hazard quotient approach, measured concentrations of chlorpyrifos and endosulfan in surface waters suggest potential hazards to aquatic organisms and were, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…They concluded that concentrations determined may negatively affect marine plant communities (including coral symbionts) and given that over 70% of samples contained more than two herbicides, mixture toxicity should be addressed . This has been supported by previous reports of herbicide mixtures detected in the environment elsewhere (Carriger and Rand, 2008;. While the herbicides in the GBR lagoon may originate from a variety of sources (e.g.…”
Section: Herbicides Detected In the Gbrsupporting
confidence: 83%
“…They concluded that concentrations determined may negatively affect marine plant communities (including coral symbionts) and given that over 70% of samples contained more than two herbicides, mixture toxicity should be addressed . This has been supported by previous reports of herbicide mixtures detected in the environment elsewhere (Carriger and Rand, 2008;. While the herbicides in the GBR lagoon may originate from a variety of sources (e.g.…”
Section: Herbicides Detected In the Gbrsupporting
confidence: 83%
“…Taking into account that endosulfan levels have been reported in the range from 0.1 to 26 lg L -1 in ground and surface water near agroecosystems (Baudino et al 2003;Dalvie et al 2003;Wan et al 2005b;Leong et al 2007;Carriger & Rand 2008;Woudneh et al 2009;Leadprathom et al 2009), bioconcentration in embryos and larvae of R. arenarum could occur. Moreover, this phenomenon could be amplified by biomagnification and thus become a great concern not only as a risk to R. arenarum populations, which normally develop in those ecosystems, but also to trophically associated species.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, these agroecosystems are continuously exposed to different types of toxic residues pesticides being relevant contaminants. The impact of endosulfan on Argentinean agroecosystems was significant in 2010 when 5.5 million liters of endosulfan were applied (CASAFE 2012) and residues frequently found in the environment in the range of 0.01-26 lg L -1 (Baudino et al 2003;Dalvie et al 2003;Wan et al 2005b;Leong et al 2007;Carriger and Rand 2008;Woudneh et al 2009;Leadprathom et al 2009;Etchegoyen 2014).…”
mentioning
confidence: 99%
“…For LC 50 or EC 50 , only 24-96 h durations were included in the SSDs for fish, crustaceans, mollusks, and noncrustacean invertebrates, whereas durations up to 168 h were included in SSDs for hydrophytes and algae. At least four species should be included in the SSDs to represent species distribution of the ecosystem (Aldenberg 1993;Carriger and Rand 2008). When multiple toxicity concentrations were available for a given species, the geometric mean was taken (Solomon et al 2000).…”
Section: Data Sourcesmentioning
confidence: 99%